The role of the regional factor determining the local religious situation - Ryazanova, S. V. (Perm Federal Research Centre Journal, 2019)
The regional local situation is considered to be a complex phenomenon shaped under the influence of various factors. The study uses the regional aspect for the analysis as the most effective way to verify hypotheses, to take the details and specific forms into account and to escape stereotypes when perceiving religious phenomena. The components of the religious panorama of the region are regarded as a result of doctrines adaptation for the local historical and cultural context. The hierarchy of influential factors may vary from one region to another, but the set of factors is presented in any case the expert analysis is applied to. The region is defined on the basis of formal criteria considering historical and geographical background. The selection of factual material for further analysis is carried out through defining the concept of religion as an instrumental one. The analysis of the confessional situation implies taking into account synchronous and historical aspects of its formation and change. Basic factors that influence the religious panorama of the region include the existing geographical conditions of the territory; the intensity of globalization processes in their local variation; the ethnic structure of the population, the specific character of mating strategy, the peculiarities of economic situation and the symbolic image of the territory. The most significant characteristics to be taken into account enable to analyze religious communities and interreligious relations, as well as to apply the predictive functions of the sociology of religion.